Andean evolution of the Aluminé fold and thrust belt, Northern Patagonian Andes (38°30′–40°30′S) - Garcia Morabito, Ezequiel (2012)
The Aluminé fold and thrust belt between 38300 and 40300S is the result of two periods of progression of deformation toward the foreland. The chronology of deformation and its relationship with magmatism through time show spatially and temporally separated magmatic events closely linked to distinct deformational stages. Data presented here confirms a Late Cretaceous mountain-building phase that coexisted in space and time with an eastward arc-migration. During this stage, a belt of deformation expanded through the foreland where it produced the Southern Neuquen Precordillera. This eastern independent mountain grew separately from the main Andean axis through a combination of inversion of the old rift systems and interaction with a pre-Andean belt which acted as a foreland obstacle. On the basis of tectonostratigraphic controls we define the last Andean contractional phase between the Late Miocene and the Pliocene. This event induced the reactivation of both sectors of the fold and thrust belt with minor propagation toward the foreland, leading to the uplift of the Patagonian Andes and reshaping the Southern Neuquén Precordillera. Both intervals of shortening are separated by a period of localized extension that resulted in the development of the Collón Cura basin within this Andean segment. Here,large thicknesses of volcanosedimentary sequences accumulated contemporaneously with the extensional activity between the earliest Oligocene and the Early Miocene.